A glutamic acid producing Streptomyces sp - Chatterjee, S; Chatterjee, S P (Folia microbiologica, 1982)
Following the bioautographic technique, a strain of Streptomyces sp. has been isolated producing L-glutamic acid. The strain in able to grow and produce glutamate in mineral salt medium, but supplementation with yeast extract improved the yield.
Keywords: kultivační média; půdní mikrobiologie; Soil Microbiology; Glutamates; glutamáty; Culture Media; kyselina glutamová; Streptomyces; Glutamic Acid